Gaming technologies in the development of spine flexibility and the coordination of children and teenagers' movements in sports classes in country health camps - P.B. Volkov (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2018)
Objective: to investigate the impact of gaming technology on the development of spine flexibility and movement coordination in children and teenagers. Material and methods: the study involved children and teenagers (n = 670, age 8-12 years). The duration of the study was 2 shifts (21 days each) in a country recreation camp. There were conducted 42 lessons. In the first shift, schoolchildren (n = 330, control group) were engaged in the program of physical education of additional education. The basis of the program were the following sections: athletics, mobile and sports games, gymnastics (morning exercises), mass sports and sports events. In the second shift, schoolchildren (n = 340, experimental group) were involved in author’s program. In the control and experimental groups, the initial and final level of development of spine flexibility and coordination of movements (agility, accuracy) were assessed. Each participant is asked to perform 3 tests. The test was evaluated on a 5 point system. Results: In both groups, positive changes in the development of spinal flexibility and coordination of movements were noted. The best dynamics is shown in the experimental group. This is explained by the following factors: an increase in the number of movements during the day on a certain group of muscles (morning exercises, mobile and sports games, massage, rhythm); concentration of motor activity on the development of spine flexibility and coordination of movements; a variety of gymnastic exercises; game form of employment. Conclusions: the purposeful use of gaming technology for the development of flexibility of the spine and coordination of movements can improve the performance of children and adolescents.